1994
DOI: 10.1037/0021-9010.79.5.724
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of voir dire as a safeguard in eyewitness cases.

Abstract: This research examined the effectiveness of voir dire as a legal safeguard in eyewitness cases. For voir dire to serve as an effective safeguard, attorneys must be able to identify and excuse prospective jurors who are unable or unwilling to critically evaluate eyewitness testimony. On the basis of previous research, we hypothesized that attitudes toward eyewitnesses would correlate significantly with jurors' perceptions of defendant culpability in a case in which eyewitness identification plays a pivotal role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In addition, people can be excused through “peremptory” challenges, which permit attorneys to excuse a limited number of people at their discretion without providing a reason. Jury selection at this courthouse stage has received some empirical attention; however, the focus is typically on how challenges affect litigants ' interests in an unbiased jury and the representativeness of juries (see, e.g., Finkelstein & Levin 1997; Johnson & Haney 1994; Jones 1987; Kerr et al 1991; Narby & Cutler 1994; Nietzel & Dillehay 1982; Seltzer et al 1991; Zeisel & Diamond 1978). Although these are important questions, we know little of how individual jurors themselves view the selection process, which means we do not know how this conscripted group regards their experience of jury participation.…”
mentioning
confidence: 99%
“…In addition, people can be excused through “peremptory” challenges, which permit attorneys to excuse a limited number of people at their discretion without providing a reason. Jury selection at this courthouse stage has received some empirical attention; however, the focus is typically on how challenges affect litigants ' interests in an unbiased jury and the representativeness of juries (see, e.g., Finkelstein & Levin 1997; Johnson & Haney 1994; Jones 1987; Kerr et al 1991; Narby & Cutler 1994; Nietzel & Dillehay 1982; Seltzer et al 1991; Zeisel & Diamond 1978). Although these are important questions, we know little of how individual jurors themselves view the selection process, which means we do not know how this conscripted group regards their experience of jury participation.…”
mentioning
confidence: 99%
“…Participants' scores from the Narby and Cutler (1994) measure were combined into a single score reflecting attitudes toward eyewitness memory (α = .80).…”
Section: Methodsmentioning
confidence: 99%
“…For the attitudes-toward-DNA-evidence scale (see Lieberman et al 2008, for the complete scale), participants rated their agreement with statements such as "DNA is the most reliable type of physical evidence we have today" and "[i]f a defendant's DNA matches DNA left at the crime scene, then the defendant is guilty," on a scale from 1 (very strongly disagree) to 10 (very strongly agree). For the attitudes-toward-eyewitness scale (see Narby and Cutler 1994, for the complete scale), participants rated their agreement with statements such as "[t]he strongest evidence is provided by eyewitnesses" and "[e]yewitnesses generally give accurate testimony in trials," on the same scale.…”
Section: Juror Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, research on the predictive utility of people's attitudes toward eyewitnesses is mixed at best. For example, one study found that mock-jurors' attitudes toward eyewitnesses were not significantly correlated with their perceptions of defendant culpability in a case involving eyewitness identification evidence (Narby & Cutler, 1994). And, because the defense is restricted to striking only a small number of potential jurors, the voir dire safeguard assumes that the propensity for jurors to be unwilling or unable to scrutinize eyewitnesses is applicable to only a small fraction of jurors.…”
Section: Insufficiency Of Legal Safeguardsmentioning
confidence: 99%